2023
DOI: 10.1162/nol_a_00097
|View full text |Cite
|
Sign up to set email alerts
|

Brain Areas Critical for Picture Naming: A Systematic Review and Meta-Analysis of Lesion-Symptom Mapping Studies

Abstract: Lesion-symptom mapping (LSM) studies have revealed brain areas critical for naming, typically finding significant associations between damage to left temporal, inferior parietal and inferior fontal regions and impoverished naming performance. However, specific subregions found in the available literature vary. Hence, the aim of this study was to perform a systematic review and meta-analysis of published lesion-based findings, obtained from studies with unique cohorts investigating brain areas critical for accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Further, the left posterior insula emerged as having a slightly higher overall positive effect on model predictions than the left superior temporal gyrus. While some studies have found an association between damage in the inferior frontal gyrus and naming impairment, recent work suggests that this effect is not consistent across studies, unlike associations in temporal and inferior parietal cortex (Piai & Eikelboom, 2023). Our results further show that despite exhibiting a significant association with language impairment, perfusion in pars triangularis does not consistently predict impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the left posterior insula emerged as having a slightly higher overall positive effect on model predictions than the left superior temporal gyrus. While some studies have found an association between damage in the inferior frontal gyrus and naming impairment, recent work suggests that this effect is not consistent across studies, unlike associations in temporal and inferior parietal cortex (Piai & Eikelboom, 2023). Our results further show that despite exhibiting a significant association with language impairment, perfusion in pars triangularis does not consistently predict impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been supported that the BNT test requires the naming of a variety of tools [75]. Thus, lesions in the inferior parietal lobe could lead to naming deficits, as this area has been linked to the manipulation and word finding of hand-used tools [76]. On the other hand, a substantial amount of evidence has established the fundamental role of the inferior frontal gyrus in the speech fluency of acute patients with aphasia, which is validated by our findings well [10,15].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical settings often employ a battery of naming tasks, commonly including visual naming, verb generation, reading, and repetition [3,[5][6][7][8]. These are widely used in intraoperative language mapping [9][10][11][12][13][14], neuroimaging studies [15][16][17][18][19], neuropsychological assessments [7,20,21], and postsurgical outcome evaluation [6,8,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%